Selective Decontamination of the Digestive Tract to Prevent Postoperative Pneumonia and Anastomotic Leakage after Esophagectomy: A Retrospective Cohort Study - Robin Janssen; Frans Van Workum; Nikolaj Baranov; Harmen Blok; Jaap ten Oever; Eva Kolwijck; Alma Tostmann; Camiel Rosman; Jeroen Schouten (MDPI AG, 2021)
Infectious complications occur frequently after esophagectomy. Selective decontamination of the digestive tract (SDD) has been shown to reduce postoperative infections and anastomotic leakage in gastrointestinal surgery, but robust evidence for esophageal surgery is lacking. The aim was to evaluate the association between SDD and pneumonia, surgical-site infections (SSIs), anastomotic leakage, and 1-year mortality after esophagectomy. A retrospective cohort study was conducted in patients undergoing Ivor Lewis esophagectomy in four Dutch hospitals between 2012 and 2018. Two hospitals used SDD perioperatively and two did not. SDD consisted of an oral paste and suspension (containing amphotericin B, colistin, and tobramycin). The primary outcomes were 30-day postoperative pneumonia and SSIs. Secondary outcomes were anastomotic leakage and 1-year mortality. Logistic regression analyses were performed to determine the association between SDD and the relevant outcomes (odds ratio (OR)). A total of 496 patients were included, of whom 179 received SDD perioperatively and the other 317 patients did not receive SDD. Patients who received SDD were less likely to develop postoperative pneumonia (20.1% vs. 36.9%, p < 0.001) and anastomotic leakage (10.6% vs. 19.9%, p = 0.008). Multivariate analysis showed that SDD is an independent protective factor for postoperative pneumonia (OR 0.40, 95% CI 0.23-0.67, p < 0.001) and anastomotic leakage (OR 0.46, 95% CI 0.26-0.84, p = 0.011). Use of perioperative SDD seems to be associated with a lower risk of pneumonia and anastomotic leakage after esophagectomy.